What enabled the successful implementation of a quality certification initiative in Bhavnagar, Gujarat? A policy analysis case study. - K Shruti Lekha; Sudha Ramani; Harsha Joshi; Preet Verma; Sumit Malhotra; Tapasvi Puwar; Chandramani Kumar; Ankita Shah; Anish Sinha; Deepak Saxena (PLOS Global Public Health)
High-quality health systems are key to improving population health outcomes globally. In India, the National Quality Assurance Standards (NQAS) is a certification policy adopted by the government to improve the quality of care in public health facilities. This policy aims to assess public health facilities through a set of comprehensive, pre-defined standards derived from global best practices. However, only a small number of districts in the country have been able to effectively complete certifications as mandated. Bhavnagar, a district in the state of Gujarat in western India, is a positive deviant that has certified the majority of its primary health facilities. This study attempts to delineate factors that have led to successful quality certifications in Bhavnagar. Qualitative data was collected between December 2023-February 2024, and includes in-depth interviews of staff from state, district, and facility levels (n = 20), and group discussions with facility staff (n = 2). Data has been analysed from the lens of the 'policy triangle', comprising actors (policymakers, managers, implementers), context (political support), content (the policy and interpretation), and processes (plans, implementation, and evaluation). We found that Bhavnagar's political context is supportive of quality certifications, with the district's top managers directing the certification process. The district's mid-level operational team on quality has engaged with innovative solutions to solve checklist-related hurdles in infrastructure like establishing a temporary fire-escape or installing screens between rooms for additional space. A peer-mentoring system, wherein staff from already certified primary health facilities act as mentors to prospective ones, has been instituted. This study consolidates empirical lessons for boosting quality certifications in similar contexts. Further, it engages with quality as not just a technical issue, but a political one that is dependent on actors, their relationships, and the implementation context. In doing so, it deepens current understandings of quality improvement strategies in health systems globally.